Numerical simulation and analysis of cavitation flows in a double suction centrifugal pump. Issue 3 (15th January 2015) - Meng, G; Tan, L; Cao, S L; Jian, W; Liu, W W; Jiang, D J
Abstract: Cavitation is an unsteady phenomenon, which is nearly inevitable in pumps. It would degrade the pump performance, generate vibrations and noises, and even erode pump flow passage components. The double suction centrifugal pump at design flow rate and large flow rate is numerically simulated using the k-ω turbulence model and the mass transport cavitation model. As a result, the calculated variation of pump head with pump inlet pressure agreed well with the experimental data. The results demonstrate that the numerical model and method can accurately predict the cavitation flows in a double suction centrifugal pump. The cavitation characteristics are analysed in great details. In addition, based on the calculation results, the reason that the plunge of pump head curve is revealed. It is found that the steep fall of pump head happens when the cavity reaches the blade to blade throat and the micro-vortex group appears at the back of the blade suction side. At the same time, this practice can provide guidance for the optimal design of double suction pumps.